Engineering Yarrowia lipolytica for high-level β-elemene production via combinatorial metabolic strategies - Mingyu Dai; Qingyi Cao; Shuanglong Jia; Jiang Chen; Hui-Ying Xu; Bang-Ce Ye; Wei-Bing Liu; Ying Zhou (Synthetic and Systems Biotechnology, 2025)
β-Elemene, a pharmacologically active sesquiterpene derived from the traditional Chinese medicinal herb Curcuma wenyujin, exhibits broad-spectrum anti-tumor and anti-inflammatory activities. Currently, its commercial production relies heavily on plant extraction, a process associated with high costs and environmental burdens, limiting industrial scalability. To address these challenges, we developed a metabolically engineered Yarrowia lipolytica strain as an efficient microbial cell factory for de novo Germacrene A biosynthesis, the direct precursor of β-elemene. Through combinatorial optimization strategies—including (1) mevalonate (MVA) pathway enhancement, (2) copy number amplification of germacrene A synthase (GAS), (3) β-oxidation pathway reinforcement, and (4) introduction of the isopentenyl utilization pathway (IUP)—we significantly improved β-elemene production. The engineered strain achieved a titer of 3.08 ± 0.05 g/L in shake-flask cultures, with a yield of 51.27 ± 0.75 mg/g glucose, representing a 3.5-fold increase over the parental strain. Our work highlights the potential of Y. lipolytica as a sustainable and scalable platform for high-value sesquiterpene production, offering a viable alternative to plant-derived extraction.